2021
DOI: 10.5606/tgkdc.dergisi.2021.20886
|View full text |Cite
|
Sign up to set email alerts
|

The cost of one unit blood transfusion components and cost-effectiveness analysis results of transfusion improvement program

Abstract: Background: This study aims to analyze the cost of the entire transfusion process in Turkey including evaluation of the cost of transfusion from the perspective of hospital management and determination of savings achieved with the transfusion improvement program. Methods: Invoices, labor, material costs were calculated with micro-costing method, while general production expenses were calculated with gross costing method between January 2018 and December 2019. Unit costs for each blood product were calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…It is important to note that the increased blood product utilization may be due to the inclusion of patients with increased severity in our study. While no effect on clinical outcome was noted in either of our groups and this could have been confounded by the retrospective nature of this study, the increase in volume of blood product transfusion does have an impact on hospital resources and adds another layer of financial burden [21][22][23]. A cross-sectional survey of a randomized sample of hospital-based blood bank and transfusion service directors to determine the average price paid by hospitals to suppliers for blood products showed that the average cost for RBC was $US 343.63 ± 135, FFP $US 60.70 ± 20 and apheresis platelets to be $US 533.90 ± 69 [24].…”
Section: Discussionmentioning
confidence: 74%
“…It is important to note that the increased blood product utilization may be due to the inclusion of patients with increased severity in our study. While no effect on clinical outcome was noted in either of our groups and this could have been confounded by the retrospective nature of this study, the increase in volume of blood product transfusion does have an impact on hospital resources and adds another layer of financial burden [21][22][23]. A cross-sectional survey of a randomized sample of hospital-based blood bank and transfusion service directors to determine the average price paid by hospitals to suppliers for blood products showed that the average cost for RBC was $US 343.63 ± 135, FFP $US 60.70 ± 20 and apheresis platelets to be $US 533.90 ± 69 [24].…”
Section: Discussionmentioning
confidence: 74%
“…Cost of transfusion in Turkey has been studied by İndelen et al using the activity-based costing method in a single hospital. The researchers concluded that the cost of erythrocyte suspension was $251.18 per patient for 2019 [ 49 ]. As the definition of activity-based costing suggests, this covered all costs including staff salaries, materials, utilities, and other items, which explains why the unit cost used in our study is lower because our study was from the SSI perspective and covered only the cost of RBC acquisition and transfusion costs.…”
Section: Discussionmentioning
confidence: 99%
“…As the definition of activity-based costing suggests, this covered all costs including staff salaries, materials, utilities, and other items, which explains why the unit cost used in our study is lower because our study was from the SSI perspective and covered only the cost of RBC acquisition and transfusion costs. If we had applied the findings from İndelen et al [ 49 ], the savings from blood transfusion for Ankara Bilkent City Hospital would have reached 14,890,034 TRY (€731,988). Similar results have been observed in other healthcare systems [ 19 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…19 Bu nedenle HKY, kan bileşenlerinin akıllı kullanımı uygulamaları ile ciddi bir tasarruf sağlanacaktır. 20 Kan bileşenleri pahalıdır ve giderek sürdürülebilir kamu sağlık maliyetlerini de olumsuz etkilemektedir. 21 Sonuç olarak bu çalışmada, TXA uygulama farklılıkları arasında postoperatif kanama miktarları arasında anlamlı farklılık saptanmadı.…”
Section: Discussionunclassified